Either at left or right, both high and low frequency rTMS of dorsolateral prefrontal cortex decreases cue induced craving for methamphetamine. (14th November 2017) - Liu, Qingming; Shen, Ying; Cao, Xinyu; Li, Yongqiang; Chen, Yijiang; Yang, Wei; Yuan, Ti‐Fei
Abstract : Background and Objectives: The study is to investigate if left or right dorsolateral prefrontal cortex is important in modulating the craving to drug related cues. Methods: The present investigation examined different combinations between left/right and high/low frequency rTMS on cue induced craving to methamphetamine, with active sham rTMS on P3 region on a total of 50 subjects. Results: The results showed that either at left or right side, both high and low frequency rTMS are effective in decreasing the cue induced craving to methamphetamine. Discussion and Conclusions: In conclusion, bilateral frontal hemispheres are effective in modulating the cue induced craving to methamphetamine with rTMS. Scientific Significance: TMS targeting prefrontal cortex is effective for craving modulation; however the mechanism is more than potentiation or depression of single brain region. (Am J Addict 2017;26:776–779)